Cognitive decline due to excess synaptic Zn2+ signaling in the hippocampus - Takeda, Atsushi (Frontiers in Aging Neuroscience, 2014)
Zinc is an essential component of physiological brain function. Vesicular zinc is released from glutamatergic (zincergic) neuron terminals and serves as a signal factor (Zn2+ signal) in both the intracellular (cytosol) compartment and the extracellular compartment. Synaptic Zn2+ signaling is dynamically linked to neurotransmission and is involved in processes of synaptic plasticity such as long-term potentiation and cognitive activity. On the other hand, the activity of the hypothalamic–pituitary–adrenal (HPA) axis, i.e., glucocorticoid secretion, which can potentiate glutamatergic neuron activity, is linked to cognitive function. HPA axis activity modifies synaptic Zn2+ dynamics at zincergic synapses. An increase in HPA axis activity, which occurs after exposure to stress, may induce excess intracellular Zn2+ signaling in the hippocampus, followed by hippocampus-dependent memory deficit. Excessive excitation of zincergic neurons in the hippocampus can contribute to cognitive decline under stressful and/or pathological conditions. This paper provides an overview of the ``Hypothesis and Theory'' of Zn2+-mediated modification of cognitive activity.